Rapid Regeneration of a Neoartery with Elastic Lamellae (Adv. Mater. 47/2022). Issue 47 (24th November 2022) - Wang, Ziyu; Mithieux, Suzanne M.; Vindin, Howard; Wang, Yiwei; Zhang, Miao; Liu, Linyang; Zbinden, Jacob; Blum, Kevin M.; Yi, Tai; Matsuzaki, Yuichi; Oveissi, Farshad; Akdemir, Reyda; et al.
Abstract : Tissue Engineering In article 2205614, Anthony S. Weiss and co‐workers report a nonporous vascular graft from tropoelastin and polyglycerol sebacate that converts into a neoartery, with cellular and extracellular matrix structures approximating the native aorta. The resulting neoartery comprises an internal elastic lamina and multiple elastic lamellae sandwiched between circumferentially aligned smooth muscle cell layers. Cover design by Ziyu Wang and illustrated by Ella Maru Studio.